Forced Use of the Upper Extremity in Chronic Stroke Patients: Results From a Single-Blind Randomized Clinical Trial - van der Lee, Johanna H.; Wagenaar, Robert C.; Lankhorst, Gustaaf J.; Vogelaar, Tanneke W.; Devillé, Walter L.; Bouter, Lex M. (Stroke (1970), 1999)
Background and Purpose —Of all stroke survivors, 30% to 66% are unable to use their affected arm in performing activities of daily living. Although forced use therapy appears to improve arm function in chronic stroke patients, there is no conclusive evidence. This study evaluates the effectiveness of forced use therapy. Methods —In an observer-blinded randomized clinical trial, 66 chronic stroke patients were allocated to either forced use therapy (immobilization of the unaffected arm combined with intensive training) or a reference therapy of equally intensive bimanual training, based on Neuro-Developmental Treatment, for a period of 2 weeks. Outcomes were evaluated on the basis of the Rehabilitation Activities Profile (activities), the Action Research Arm (ARA) test (dexterity), the upper extremity section of the Fugl-Meyer Assessment scale, the Motor Activity Log (MAL), and a Problem Score. The minimal clinically important difference (MCID) was determined at the onset of the study. Results —One week after the last treatment session, a significant difference in effectiveness in favor of the forced use group compared with the bimanual group (corrected for baseline differences) was found for the ARA score (3.0 points; 95% CI, 1.3 to 4.8; MCID, 5.7 points) and the MAL amount of use score (0.52 points; 95% CI, 0.11 to 0.93; MCID, 0.50). The other parameters revealed no significant differential effects. One-year follow-up effects were observed only for the ARA. The differences in treatment effect for the ARA and the MAL amount of use scores were clinically relevant for patients with sensory disorders and hemineglect, respectively. Conclusions —The present study showed a small but lasting effect of forced use therapy on the dexterity of the affected arm (ARA) and a temporary clinically relevant effect on the amount of use of the affected arm during activities of daily living (MAL amount of use). The effect of forced use therapy was clinically relevant in the subgroups of patients with sensory disorders and hemineglect, respectively.